Propuesta de producto comunicacional que reposiciona la imagen de la carrera de comunicación social frente a estudiantes de secundaria - Vásquez Tibillin, Sara Maritza (Machala, 2019)
This project forms the last part of the titling work process that is aimed at creating a product that helps reposition the image of the social communication career in third-year high school students of the fiscal educational units of the province of El Gold. The research was carried out through bibliographic review, in articles of scientific journals and books of the UTMACH library, in turn I use the qualitative method with interviews to professional in communication and quantitative method through surveys of secondary school students; The methodology yielded valuable results, in other words it was possible to identify the social imaginary that young people have about the communication and communicators career. Stereotypes and prejudices were also known through the past experiences of the interviewees, in addition to determining the appropriate product for this project. From the above, it is proposed to develop a communication campaign that allows interaction between secondary students and university students in the execution of the different roles that the social communicator plays in the workplace.
El presente proyecto forma la última parte del proceso del trabajo de titulación que está orientado a crear un producto que ayude a posicionar la imagen de la carrera de comunicación social en los estudiantes de tercer año de bachillerato de las unidades educativas fiscales de la provincia de El Oro. La investigación se realizó mediante revisión bibliográfica, en artículos de revistas científicas y libros de la biblioteca de UTMACH, a su vez utilizó el método cualitativo con entrevistas a profesional en comunicación y método cuantitativo a través de encuestas a estudiantes de secundaria; la metodología arrojó resultados valiosos, dicho de otra manera se pudo identificar el imaginario social que tiene los jóvenes acerca de la carrera de comunicación y de los comunicadores. También se conoció los estereotipos y prejuicios mediante las experiencias pasadas de los entrevistados, además de determinar el producto adecuado para este proyecto. De lo expuesto anteriormente se propone la elaboración de una campaña comunicacional que permita la interacción entre estudiantes secundarios con universitarios de la carrera en la ejecución de los distintos roles que cumple el comunicador social en el ámbito laboral.
Keywords: COMUNICACION; PRODUCTO COMUNICACIONAL; IMAGINARIO SOCIAL